일반소비자 입장에서 이동통신 유통구조 인식에 관한 연구 - 황동현(Dong Hyun Hwang); 김무연(Moo Yeon Kim); 최성진(Seong Jhin Choi) (디지털콘텐츠학회논문지, 2019)
국내 이동통신시장에서 단통법은 2019년 세계최초 상용화한 5G서비스 개시까지 시장 과열 및 불법 보조금 기승으로 인해 유명무실하게 되었다. 치열한 단말기 보조금 위주의 정책을 벌이는 근본적 원인은 일정기간 동안 서비스 사용을 약정하여 보조금을 지급하는 단말기와 서비스 묶음판매 유통구조 때문이다. 본 연구에서는 일반소비자 입장에서, 단말기 유통구조의 인식과 소비자 불만족이 완전자급제에 어떠한 영향을 미치는 지에 대해 분석한 후, 유통구조 개선을 위한 바람직한 정책대안을 제시하였다. 실증적 연구를 위한 연구모형 및 가설을 수립하고, 설문조사를 활용하여 분석한 후 정책적으로 단말기와 서비스의 완전분리제가 요구됨을 제기하였다. 이에 따라 경쟁을 촉발하여 소비자 효용이 증대되고, 소비자 보호가 제도적으로 정착될 것으로 예상된다. In the domestic mobile telecommunication market, mobile device distribution improvement act became meaningless due to overheated market and the rise of illegal subsidies until the launch of the world's first commercialized 5G service in 2019. The fundamental cause of the fierce handset subsidy-oriented policy lies in the distribution structure of handset and service bundle, which provide subsidies by agreeing to use the service for a certain period of time. This paper aims to present a desirable policy alternative for improving the distribution structure after analyzing how the recognition of the distribution structure of the handset and consumer dissatisfaction affect the complete unbundling handset and mobile service. To this end, the research model and hypotheses for empirical research were established, analyzed using the latest survey, and raised the need for a complete separation of handsets and services. As a result, it is expected that consumer efficiency will be increased by triggering competition, and eventually consumer protection will be established systematically. KCI Citation Count: 0